Feed Composition And Nutrition Affecting Duck Egg Quality In Central Java Intensive Farming, Indonesia - R.Susanti; Endah Yuliana; Muchamad Dafip (Jurnal Biodjati, 2025)
Various feeds are widely used to increase egg productivity in the Central Java duck-intensive farming system. However, the proper composition and nutrition in the feed are still debatable. This study aims to analyze the applied feed composition and nutritional content related to duck egg quality from intensive Central Java farms. This research is an observational, exploratory survey involving duck farms in five egg duck production centers, including Semarang, Temanggung, Magelang, Pati, and Salatiga regions. The feeds and 10 duck egg samples were collected from each farm to identify the raw nutritional content and quality. The result showed that the duck feed composition differs depending on the abundance of local resources and farmers’ knowledge. Duck farms in coastal areas mainly use fishery products, including small rough fish and dried shrimp waste, while farmers in highland areas prefer to use commercial feed. Farmers in all regions often supplement their diets with additional feed, such as water spinach, rice bran, snails, wrinkles, and weeds, for varying durations from every day to once a week. Meanwhile, the best feed nutrition was identified from Temanggung, which uses concentrate feed as the main diet, which is composed of sweet corn, soy, and bran. The feed has a balance of raw protein around 24.19 ± 4.11% and 2500 to 2700 kcal calories. The egg productivity in the Temanggung farms also produces high egg production with larger sizes compared to duck farms from other regions. Furthermore, corn and soybeans in duck feed may increase antioxidant activity in yolk significantly, better than shrimp waste.